Impact of subthalamic nucleus stimulation did not differ on young-onset and older-onset Parkinson's disease: A three-year follow up. (13th July 2019) - Zhang, Junmei; Jia, Ge; Yang, Zhuanyi; Liu, Dingyang; Hou, Yonghong; Wang, Yanjin; Yang, Zhiquan
Highlights: A three-year retrospective cohort study is conducted. The different impact of STN-DBS on YOPD and OOPD patients with an onset age cut-off of 50 years is first demonstrated. STN-DBS alleviates motor symptoms and improves quality of life equally in both YOPD and OOPD patients. Abstract: Objective: To assess the role of onset age in the results of bilateral subthalamic nucleus deep brain stimulation (STN-DBS), we carried out a retrospective study of two groups of patients regarding age at disease onset. Methods: We compared, up to 3 years after surgery, the clinical effects, quality of life and the levodopa equivalent daily dose (LEDD) in patients with young-onset Parkinson's disease (onset age <50 years, YOPD) vs patients with older-onset Parkinson's disease (onset age ≥50 years, OOPD). Results: A dramatic improvement in motor symptoms was equally observed in both groups of patients after DBS. The improvements of the Unified Parkinson's Disease Rating Scale part III motor scale (UPDRS-III) score, axial sub-score and non-axial sub-score from baseline gradually decreased over time. The benefit of STN-DBS for the axial symptoms decreased most rapidly, which directly resulted in a progressive decline in stimulation efficacy in both groups. Nevertheless, the improvement in non-axial symptoms after DBS was remarkable and long-lasting. The quality of life in both groups were also improved after DBS but were slightly decreased in the following years. The reduced LEDD were equivalent in both groups. Conclusions: STN-DBS alleviates motor symptoms and improves quality of life equally in both YOPD and OOPD patients with similar LEDD. The initial therapeutic benefit of STN-DBS for PD gradually decreases over time, mainly due to the progression of PD and the rapid withdrawal of the benefit for axial symptoms.